2018
DOI: 10.1016/j.dadm.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Understanding hallucinations in probable Alzheimer's disease: Very low prevalence rates in a tertiary memory clinic

Abstract: Introduction Averaging at 13.4%, current literature reports widely varying prevalence rates of hallucinations in patients with probable Alzheimer's disease (AD), and is still inconclusive on contributive factors to hallucinations in AD. Methods This study assessed prevalence, associated factors and clinical characteristics of hallucinations in 1227 patients with probable AD, derived from a tertiary memory clinic specialized in early diagnosis of dementia. Hallucinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Atrophy of the right anterior insula in patients with Alzheimer's disease is related to their experience of hallucinations, which is a major symptom of dementia [68,69]. Patients who experience hallucination achieve lower scores on the MMSE [69]. The previous observations agree with the present findings that high-frequency oscillatory intensity in the right anterior insula correlates with scores on the MMSE.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Atrophy of the right anterior insula in patients with Alzheimer's disease is related to their experience of hallucinations, which is a major symptom of dementia [68,69]. Patients who experience hallucination achieve lower scores on the MMSE [69]. The previous observations agree with the present findings that high-frequency oscillatory intensity in the right anterior insula correlates with scores on the MMSE.…”
Section: Discussionsupporting
confidence: 90%
“…Atrophy of the right anterior insula in patients with Alzheimer's disease is related to their experience of hallucinations, which is a major symptom of dementia [68,69]. Patients who experience hallucination achieve lower scores on the MMSE [69].…”
Section: Discussionmentioning
confidence: 99%
“…Visual hallucinations are rare in MCI but become more common in all-cause early dementia [55]. One large study based in a specialist early AD clinic found very low rates of VH, and the authors commented that VH seemed to be more prevalent in the later stages of the illness [56], perhaps reflecting cholinergic denervation in areas of the cortex affected later on than the temporal lobe. EEG slowing in AD and visual hallucinations was interpreted as a potential neurophysiological indicator of cholinergic deficiency [57].…”
Section: Discussionmentioning
confidence: 99%
“…Older people with psychotic symptoms or late‐onset psychotic disorders are at 2.5 to 8 times higher risk to develop dementia compared with those without these symptoms depending on observation time and age . Delusions and hallucinations may also be part of the prodromal stage of dementia, although it is debated how often it occurs in early Alzheimer's disease (AD) .…”
Section: Introductionmentioning
confidence: 99%